Teaching in different ethos of choise: a comparison of two countries (La enseñanza en diferentes tipos de instituciones: Comparación en dos países) (L'enseignement dans différents types d'institutions: Comparaison entre deux pays) (O ensino em diferentes tipos de instituições: comparação em dois países) - Nina K. Buchanan (Pontificia Universidad Javeriana, 2009)
Current educational research often incorporates an unconscious cultural or national bias that starts from the questions which are asked and concludes with the implications which are drawn. We describe a three-month in situ study of ethos in Irish National Primary Schools and attempt to identify how US and Irish professional teaching practices reflect the political and educational ethoi (customs) of their respective homes. In this paper, we focus on what is revealed about teacher practices and professional life: teacher views of school choice, the teachers' role in the operation of schools, the national curriculum, and student assessment.